CARING OF INPATIENT NURSES WITH THE FAMILY'S READINESS TO RECEIVE MEDICAL INFORMATION ABOUT ADVANCED THERAPY - Susiana, Farida; Elliana, Agusta D. (SYNTHESIS Global Health Journal, 2024)
Background. Caring is the basis for nurses to be able to analyze nursing actions carried out well and appropriately for clients which becomes a reference in further care. In other words, caring is the moral ideal of the nursing profession which refers to the willingness to provide sincere care with seriousness in carrying out actions to care for clients' health. Research Method. A literature search in this research was carried out by identifying all types of national and international articles regarding caring for community nurses and the readiness of families to receive further therapy information The electronic databases used were PubMed, Springer, and Google Scholar with 30 articles then filtered into 3 articles with a search strategy using the PICO method (patient, intervention, comparison and outcome).  Findings. Participants expressed that caring is an attitude of empathy, caring about patient needs, providing nursing care not only when patients come to the health center but also when nurses provide home care. Participants expressed caring behavior such as empathy, being friendly to patients who came to the treatment center, caring about patient needs, making home visits to patients, paying attention to the patient's health needs. Conclusion. Caring for inpatient nurses is an effort to improve the performance of nurses in providing nursing services to patients so as to create integrated and comprehensive care for patients. By increasing professional patient-nurse relationships, participants said they were helped by getting to know the many patients who came for treatment at the health center.